QTL analysis identifies multiple behavioral dimensions in ethological tests of anxiety in laboratory mice. - Turri, MG; Datta, SR; DeFries, J; Henderson, N; Flint, J (2001)
BACKGROUND: Ethological tests of anxiety-related behaviors, such as the open field arena and elevated plus maze, are often carried out on transgenic animals in the attempt to correlate gene function with a behavioral phenotype. However, the interpretation of such tests is problematic, as it is probable that different tests measure different aspects of behavior; indeed, anxiety may not be a unitary phenomenon. Here, we address these questions by asking whether behaviors in five ethological tests of anxiety are under the influence of a common set of genes. RESULTS: Using over 1600 F2 intercross animals, we demonstrate that separate, but overlapping, genetic effects can be detected that influence different behavioral dimensions in the open field, elevated plus maze, square maze, light-dark box, and mirror chamber. We find quantitative trait loci (QTLs) on chromosomes 1, 4, and 15 that operate in four tests of anxiety but can be differentiated by their action on behavior in threatening and nonthreatening environments and by whether habituation of the animals to an aversive environment alters their influence. QTLs on chromosomes 7, 12, 14, 18, and X influenced a subset of behavioral measures. CONCLUSIONS: The chromosome 15 QTL acts primarily on avoidance behavior, the chromosome 1 QTL influences exploration, and the QTL on chromosome 4 influences activity. However, the effects of loci on other chromosomes are not so readily reconciled with our current understanding of the psychology of anxiety. Genetic effects on behaviors in these tests are more complex than expected and may not reflect an influence on anxiety.